Learning Strategies at SD Muhammadiyah Ngoro During the Covid-19 Pandemic - Diana Angellina; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to describe the learning strategies during the Covid-19 pandemic at SD Muhammadiyah Ngoro. This research uses descriptive qualitative method. The informant in this case is a teacher at SD Muhammadiyah Ngoro. Data collection techniques used include interviews, observation and documentation. Data analysis using data presentation techniques and drawing conclusions. The results of this study indicate that learning strategies in the midst of the Covid-19 pandemic include 1) online and offline learning strategies. 2) by door-to-door or the teacher visiting each student's house 3) students enter school with alternating schedules during pendemi 4) students come directly to school to collect assignments.